Analisis Pemahaman Quality Assurance pada Mahasiswa Bisnis Digital Universitas Pendidikan Indonesia - Gieldy Akhyat Affandi Utama; Adam Hermawan; Adi Prehanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digital Business students at Universitas Pendidikan Indonesia Tasikmalaya Campus recognize the importance of Quality Assurance (QA), but many do not fully grasp the concept. This study aims to describe and evaluate students’ understanding of QA, with the goal of bridging the gap between awareness and application in the field of Digital Business. The research method used is descriptive quantitative, employing a Probability Sampling technique with a Proportionate Stratified Random Sampling approach. Results indicate that students generally have a good understanding of QA, especially in grasping basic concepts and the significance of QA for product quality. However, some dimensions of QA remain less understood, particularly regarding practical application in the industry. The depth of understanding varies; most students have a sufficient basic grasp, but only a few can relate QA concepts to real-world case studies. Based on these findings, the Digital Business Study Program is advised to integrate practical elements into the QA curriculum, such as QA simulations, industry case studies, and collaborative projects with companies. This is expected to enhance students’ understanding and bridge the gap between QA theory and practice. Future research could test the effectiveness of various QA teaching approaches and compare understanding across different study programs. duk